The complete chloroplast genome sequence of the Citrullus colocynthis L. (Cucurbitaceae). Issue 2 (12th December 2017) - Zhu, Qianglong; Zhang, Muyue; Cui, Haonan; Fan, Chao; Gao, Peng; Wang, Xuezheng; Luan, Feishi
Abstract: Citrullus colocynthis L. is one of the worldwide famous traditionally medicinal plants and widely applied in watermelon breeding for its multiple resistances. The complete nucleotide sequence of desert watermelon ( Citrullus colocythis L.) chloroplast genome has been determined in this study. The genome was composed of 157, 147 bp containing a pair of inverted repeats (IRs) of 26, 149 bp, which was separated by a large single-copy region of 86, 851 bp and a small single-copy region of 17, 998 bp. A total of 123 genes were predicted including 86 protein-coding genes, eight rRNA genes and 29 tRNA genes. Phylogenetic analysis revealed that C. colocynthis were closely related to other two species in the genus Citrullus . The complete chloroplast genome of C. colocynthis would provide some significant information for Cucurbitaceae evolutionary and genomic studies.